2007
DOI: 10.1183/09031936.00015207
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and functional activity in superoxide dismutase and catalase genes in smokers with COPD

Abstract: Increased oxidative stress has been implicated in the pathogenesis of chronic obstructive pulmonary disease (COPD). This study investigated the risk of COPD and the substitution of alanine 16 with valine (Ala16Val) polymorphism of manganese-superoxide dismutase (Mn-SOD) and the cytosine to thymidine transition of nucleotide -262 (-262C.T) polymorphism of the catalase gene, and the activity of erythrocyte SOD and catalase.The subjects were stable COPD patient ever smokers (n5165) and healthy controls, matched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
6
36
2
2
Order By: Relevance
“…Consistent with our result, a study in erythrocyte red blood cells showed decreased CAT activity in patients with COPD [35,36]. In contrast, a study on single nucleotide polymorphism in CAT gene (-262 C > T) showed that erythrocyte catalase activity was higher in COPD patients with the C/C genotype, and with the combined C/T and T/T genotypes, than in healthy controls [37]. Our study supports the finding of Tavilani et al, which reported an increase in SOD and CAT activities in alveolar macrophages of elderly smokers [38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our result, a study in erythrocyte red blood cells showed decreased CAT activity in patients with COPD [35,36]. In contrast, a study on single nucleotide polymorphism in CAT gene (-262 C > T) showed that erythrocyte catalase activity was higher in COPD patients with the C/C genotype, and with the combined C/T and T/T genotypes, than in healthy controls [37]. Our study supports the finding of Tavilani et al, which reported an increase in SOD and CAT activities in alveolar macrophages of elderly smokers [38].…”
Section: Discussionsupporting
confidence: 90%
“…However, we found a dramatic increase in SOD and CAT activities among patients with more severe COPD. It was found that erythrocyte SOD and CAT activities gradually increased from GOLD stages I to IV in COPD patients, which is supported by previous reports [36][37][38][39][40][41]. Indeed, various studies [40][41][42] except one study [7] have suggested that certain markers of oxidative stress may be related to tobacco smoking or to the severity of COPD.…”
Section: Discussionsupporting
confidence: 73%
“…An association of the Ala16Val SNP was not found neither with the presence of COPD nor with lung function decline, which is in concordance with results of two previous studies performed [18,19].…”
Section: Sod Genetics In Copd and Bhr M Siedlinski Et Alsupporting
confidence: 91%
“…Ala16Val, which is localised in a protein signal sequence, and thus possibly has a functional role [12][13][14]. This substitution has been associated with a higher lung cancer risk in Caucasians [15][16][17] but not with the presence of COPD in Caucasian and Chinese smokers [18,19]. SOD3 contains three nonsynonymous SNPs, i.e.…”
mentioning
confidence: 99%
“…Various inflammatory and structural cells in the airways have been reported to generate increased amounts of ROS [2]. The lungs have developed several endogenous antioxidant systems to deal with the production of free radicals [3]. Superoxide dismutase (SOD) catalyses the dismutation of O 2 ⋅ -to H 2 O 2 and oxygen (O 2 ), while catalase (CAT) decomposes H 2 O 2 to water and oxygen.…”
Section: Original Papersmentioning
confidence: 99%